Rock Glaciers in the Patagonian Andes: An Inventory for the Monte San Lorenzo (Cerro Cochrane) Massif, 47° S - Falaschi, Daniel (2015)
Although rock glaciers in the Central and Desert Andes of Argentina and Chile have been previously studied in detail, much less attention has been paid to the occurrence of these permafrost forms in Patagonia. Recently, however, the establishment of the Argentinean Glacier Inventory program, which intends to inventory and monitor all ice masses along the Argentinean Andes, has started a large amount of new geocryological research. The project is designed to provide reliable and worldwide comparable results, supported by well established technical procedures and background information. Presented here is the first rock glacier inventory of the Monte San Lorenzo (Cerro Cochrane) region in the southern Patagonian Andes. A total of 130 intact (9.86 km2) and 47 fossil (1.45 km2) landforms were inventoried using two 2.5 m resolution ALOS Panchromatic Remote-sensing Instruments for Stereo Mapping images. Since the Argentinean federal initiative described above legally protects all rock glaciers in the country as water reserves, and due to the little scientific knowledge concerning rock glaciers in the vast majority of the Patagonian Andes, this inventory provides an important basis for political decision-making and opens further geocryological research avenues for the Patagonian region in general.